Morte violenta de mulheres no Brasil e novas vulnerabilidades : da violência do patriarcado privado à violência do patriarcado público - Lucena, Mariana Barrêto Nóbrega de (2020)
With the objective of bringing new contributions to studies on homicide against women in Brazil, this work proposes to undertake an analysis that makes explicit the changes and permanencies pertinent to female vulnerability to lethal violence; exposing manifestations that diverge from the standards of femicide as provided for in Brazilian criminal law, as well as presenting how lethal gender violence unfolds today, placing the theme within the current dynamics of patriarchy, capitalism, and racism. A current assumption in studies on homicides of women is questioned, which states that women die mainly due to domestic violence, or other aggressions of a sexual nature. It is therewith assumed that in the current context of the systems of oppression of gender, class and race, it is no longer possible to make inferences of this type. It is argued that from their insertion into public spaces, arrives their greater susceptibility to the market and to the State (being patriarchal, neoliberal, and racist), and in this context, that the war on drugs being a strategy of social neutralization, then produces new vulnerabilities to violence, making such aggressions more diverse than is supposed. To verify this hypothesis, quantitative-qualitative research was carried out based on police investigations of homicides against women, between 2013 and 2017, in the cities of João Pessoa and Porto Alegre. In quantitative analysis, we sought primarily to identify the motive for each crime and the use of sexual violence in the practice of the crime, relating these data to other situational elements, the profile of the victim, and to aspects concerning the perpetrator of the crime (when possible to identify). It was identified that femicide - operationalized as a crime motive based on gender and/or using sexual violence - was responsible for 14.3% of homicide cases in each of the two cities studied, below the roughly 40% presented in several other studies. Homicides motivated by conflicts related to drug trafficking, without the presence of sexual violence, were mostly responsible for the deaths of the women, victimizing 55.5% of women in Porto Alegre and 39.7% in João Pessoa. In qualitative analysis, we sought to deepen and bring certain reflections concerning the data collected, performing counterpoints to previous research related to the theme. Among points, it is emphasized that femicide, although less prevalent in the two cities studied than in certain other cities, notably continues against women, and more than an exercise of violence against a fragile, and dependent woman, restricted to the home, it acquires manifestations that represent a reaction to both female empowerment and lost male power.